Early Results of High Tibial Osteotomy for Osteoarthritis in Mongolia - Boldbayar, Tuvshinjargal; Sodnompil, Dashtsogt; Narangerel, Enkhtaivan; Ulziibat, Bayartsengel; Maidar, Otgonbayar; Orgoi, Sergelen (Central Asian Journal of Medical Sciences, 2019)
Objectives: The objectives of this study were to examine the reproducibility of the surgical correction and pain relief following high tibial osteotomy for osteoarthritis. Methods: Twenty-seven patients who underwent high tibial osteotomy at The First Central Hospital of Mongolia were included. Patients divided into three groups based on their osteoarthritis grade using the Kellgren Lawrence classification. The weight-bearing line and medial proximal tibial angle were used for preoperative planning to assess postoperative correction. Oxford knee scores were used to assess knee pain and function. Results: The weight-bearing line and medial proximal tibial angle measurements at both postoperative time intervals were significantly different from the preoperative values (p<.001) but were not significantly different from each other. The Oxford knee scores were 31.54±6.3 preoperatively, 34.82±4.3 at two months after the surgery and improved to 40.89±2.7 six months after the surgery. Statistically significant successive improvements in scores were observed at each time interval (p<.001). Conclusion: High tibial osteotomy can be done with rigid internal fixation and can improve function and reduce pain in Mongolian patients with early arthritis without affecting joint range of motion.